Hubungan Pola Asuh Orang Tua Dengan Perkembangan Motorik Halus Balita Di Posyandu Gonilan, Kartosuro - Wiratini, Rindang; , dr. Mohammad Shoim Dasuki, M. Kes; , dr. Anika Candrasari, M.Kes (2015)
Background : Parenting pattern was an interaction berween parent and children, there was four types of parenting pattern, such as authotarian, permisif, authoritative mixture. Parenting pattern has become one of factor that influence fine motor addaptive on children. Fine motor addaptive was a smooth coordination of small muscles. Aim : To know the assosiation of parenting parents with fine motor addaptive in Posyandu Gonilan, Kartasura. Methods : The study used analytic observasional design with cross sectional methods. The study was held in Januari - Februari 2015 in Posyandu Gonilan, Kartasura. Sample used in this research was a mother who had 12 until 48 months childrens. Samples were taken using purposive sampling. The realtionships of parenting parents with fine motor addaptive in Posyandu Gonilan Kartasura as analyzed with Chi - Square test using SPSS program 17 for Windows. Result : Good parenting pattern which applied by parents was 64,29% and fine motor addaptive which based on age was 53.58% Conclution : There is assosiation of parenting parents with fine motor addaptive in Posyandu Gonilan, Kartasura